(untitled) - Needham, Joseph (Cambridge, 1966)
This book introduce the morphogenetic substratum, the morphogenetic stimuli, the morphogenetic mechanisms. Glossary of some of the spechial terms used in thisc work.
Keywords: Hóa sinh học,Biochemistry